Use of technologies in Brazilian public higher education in times of pandemic COVID-19 (Research, Society and Development, 2020)
The year 2020 is already marked as the year of the pandemic COVID-19. This pandemic has been changing the socioeconomic structures of the world, and educational institutions in Brazil practically had to interrupt their face-to-face activities due to the rules of social distancing. According to the teaching method, technology-mediated learning has gained emphasis and makes room for differentiated human interactions. These teaching methodologies already existed, but they still reached a small scale. This article presents and discusses the Brazilian perspectives on the challenges and opportunities for the use of educational technologies for public higher education.  The main results indicate that the implementation of digital inclusion policies, aiming to reduce regional inequalities of internet access, is a necessary condition for any remote teaching strategy to be successful.